The problem of uncertainty of strength parameters for numerical simulation of dynamic limestone fracture - Borodin, Elijah Nikolaevich; Abramyan, Andrey Karenovich (Computational Continuum Mechanics, 2017)
Limestone is one of the most important construction materials and at the same time is of great interest from the mechanical point of view, as a natural material with a large volume fraction of pores. There are major difficulties for numerical simulation of its fracture process, especially at high strain rates, due to a complex internal microstructure and uncertainty of its mechanical characteristics. It makes the results of numerical simulation is largely arbitrary and detached from a particular experiment. Structural and microstructural observations can provide a substantial support for the numerical studies. The paper demonstrates some effects that occur at numerical simulation of dynamic loadings of the limestone samples in the Hopkinson-Kolsky bars. We describe different modes of fracture of the porous limestone samples and their corresponding deformation curves. It is shown that the macroscopic three-dimensional effects (because of reflections of shock waves from the free surfaces of the sample) and the consequent changes of fracture modes in the conditions of general uncertainty of the mechanical characteristics of the material may significantly exceed more subtle microstructural effects. At the same time, such fracture mode changes can help one to determine the material parameters.